Peningkatan Motivasi Belajar Siswa Kelas IX dengan Pendekatan Bermain pada Mata Pelajaran PJOK di SMP Negeri 28 Surabaya - Fifi Alfiah; Bambang Ferianto Tjahyo Kuntjoro (Simpati, 2024)
One way to increase children's physical activity is through learning Physical Education, Sports and Health (PJOK) at school. Considering the characteristics of junior high school students aged 12-15 years who tend to like to play, this approach can be very effective. Children generally enjoy fun activities such as playing, which can motivate them to participate in physical activities and keep their bodies fit and healthy. This research used the Classroom Action Research method which was carried out in two cycles, with each cycle consisting of two meetings regarding physical fitness material. Data was collected through observation, documentation and questionnaires to evaluate students' opinions about the learning carried out. The research results showed that the play approach proved to be very effective in increasing PJOK learning motivation in class IX of SMP Negeri 28 Surabaya. Therefore, it is important to develop innovation in PJOK learning so that students are more interested and involved in this activity.